2008
DOI: 10.1590/s0004-27492008000400004
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression of VEGF, IGF-1 and FGF in retroocular connective tissues and clinical correlation in Graves' ophthalmopathy

Abstract: 5) (45.4%). VEGF: There were two positive cases (8.3%) for VEGF in endothelial cells, in these cases the patients also presented CAS higher than 5. There was no expressions of all growth factors in the control group. CONCLUSIONS: All patients, except one, with positive expression of FGF, IGF-1 and VEGF showed CAS greater than 5, suggesting in this way an important role of these growth factors in the pathogenesis and severity of Graves' ophthalmopathy. However, statistical analysis revealed only significant ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
(30 reference statements)
1
13
0
Order By: Relevance
“…Previous work has shown that incubation of orbital fibroblasts from GO patients with PDGF‐BB may enhance the expression of the thyroid‐stimulating hormone receptor (TSHR) . Another study showed that there may be a correlation between EGF and GO, although this remains uncertain . Eotaxin‐3 and MIP‐3‐alpha belong to another cytokine family; to date, no studies have been undertaken on their involvement in GD or GO.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that incubation of orbital fibroblasts from GO patients with PDGF‐BB may enhance the expression of the thyroid‐stimulating hormone receptor (TSHR) . Another study showed that there may be a correlation between EGF and GO, although this remains uncertain . Eotaxin‐3 and MIP‐3‐alpha belong to another cytokine family; to date, no studies have been undertaken on their involvement in GD or GO.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, VEGF is a vital factor in the inflammatory process and wound healing response [29,30], and it is present in extraocular muscle and retroorbital tissue [31]. Therefore, we expect that bevacizumab will be a useful future treatment modality in intraocular or extraocular ocular disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Our study supports the observations of other authors. Matos and al. found that patients with positive expression of FGF, IGF-1 and VEGF in extraocular eye muscles showed CAS greater than 5, suggesting in this way an important role of these growth factors in the pathogenesis and severity of TO [ 30 ] . Platelet-derived growth factor (PDGF) is a homodimeric protein centrally involved in wound healing and fi brotic diseases by stimulating chemotaxis, proliferation, and extracellular matrix production by mesenchymal cells, such as fi broblasts [ 31 , 32 ] .…”
mentioning
confidence: 83%